Improving seed germination: effect of stratification and dormancy-release priming in Lonicera insularis Nakai - Lee, Jihun; Park, Kyungtae; Lee, Hamin; Jang, Bo-Kook; Cho, Ju-Sung (Frontiers in Plant Science, 2024)
Lonicera insularis Nakai is endemic plant predominantly distributed along the coastlines of Ulleungdo and Dok-do in South Korea, and is significant for medicinal and ornamental uses. However, previous studies reported that L. insularis seeds exhibit morphological dormancy (MD), causing them to germinate only at specific temperatures. Therefore, this study aimed to classify the dormancy type of L. insularis seeds, expand the germination temperature range, and confirm the industrial applicability through dormancy-release (DR) priming. The seeds of L. insularis exhibited no inhibition of water absorption by the seed coat, with 85.0 % germination observed at 15℃, similar to the viability (84.0%). Initially, the initial seeds of L. insularis exhibited an embryo-to-seed (E:S) ratio of 0.24 during dispersal, which increased to 0.81 by day 18 at 15℃, indicating that the seeds exhibit MD with underdeveloped embryos. Treatments with GA3 and GA4+7 to overcome MD and expand the germination temperature range did not significantly enhance germination. However, seeds that grew embryos through stratification for 2 weeks at 15℃ effectively expanded the germination temperature range. Additionally, DR-primed seeds maintained the expanded germination temperature range even after redrying, confirming the commercial potential of DR-primed seeds. Therefore, this study represents the first application of a novel approach to alleviate dormancy in L. insularis seeds through the integration of stratification and priming techniques, termed dormancy-release priming. This approach resulted in a significant increase in germination and expanded the effective temperature range for seed germination. These findings suggest that dormancy-release priming could be a valuable method for producing non-dormant seeds, enhancing the potential for L. insularis distribution and industrial applications.